Treatment outcome of drug-resistant tuberculosis (DR-TB) following uptake of universal drug susceptibility testing: A record review from a nodal DR-TB center - Bharti, Aditi; Akanksha Tomar,; Tiwari, Rajesh (Asian Journal of Medical Sciences, 2023)
Background: There has been delay evident in diagnosing the drug resistance and non-initiation of appropriate treatment based on drug susceptibility pattern resulting in poor treatment outcome of drug-resistant tuberculosis (DR-TB). Aims and Objectives: The aims of this study were to examine the treatment outcomes for DR-TB patients following universal drug susceptibility testing (UDST) and to examine the association of sociodemographic, behavioral factors, or comorbidities with outcome. Materials and Methods: A retrospective study at a nodal DR-TB center was done for the past 2 years (2018–2019) following the district’s adoption of UDST. The study comprised patients registered between January 2018 and December 2019. Transferred out cases were excluded from the analysis. Cured or treatment completed were assigned as successful, whereas the treatment failed, lost to follow-up or died were adverse treatment outcome. Results: A total of 201 patients were initiated on suitable DOTS regime and they continued the treatment from the center, during the study period. Altogether 129 (64.2%) patients had successful treatment outcome. None of the examined variable (age, sex, SES, Body mass index, and comorbidity) is found to have statistically significant association with outcome (P>0.05). Conclusion: The UDST may be the reason for success rate shown here, higher than in literature published. Although a better stance is possible only by comparing the treatment outcome of pre- and post-uptake of UDST from same setting.